Total Single-Stage Autologous Breast Reconstruction with Free Nipple Grafts - Schwartz, Jean-Claude D. (Plast Reconstr Surg Glob Open, 2016)
Outstanding results are difficult to achieve in postmastectomy reconstructions in obese ptotic patients. We describe an autologous single-stage reconstruction with free nipple grafts that is best suited for these difficult patients. This technique allows for delayed volume supplementation with implants or fat grafting but does not commit the patient to additional surgery. It avoids the common complications of immediate implant-based reconstructions. This technique is also an excellent option in patients with a known requirement for radiotherapy as it does not sacrifice a valuable autologous flap nor does it subject the patient to capsular contracture, infection, and extrusion. It also obviates the psychological trauma that many women suffer awaiting a reconstruction after radiotherapy. We believe it should be considered as a first-line reconstructive option.